Extensive novel waves evolution of three-dimensional Yu-Toda-Sasa-Fukuyama equation compatible with plasma and electromagnetic applications - Rashed, A. S.; İnç, Mustafa; Saleh, R. (World Scientific Publ Co Pte Ltd, 2023)
There is no doubt that the investigation of the interaction and propagation of plasma and electromagnetic waves play an important role in understanding these phenomena. The three-dimensional Yu-Toda-Sasa-Fukuyama equation (YTSFE) is a competent mathematical model of waves in plasma, electromagnetics, or fluids. An optimal system of infinitesimal symmetries is constructed to discover extensive and astonishingly exact solutions to the YTSFE. The outstanding solutions include periodic, polynomials, fractional, logarithmic, exponential, hyperbolic, exponential integral, Airy and complex functions. These solutions are significant because they help understand how plasma and electromagnetic applications work at different boundary or initial conditions.
Keywords: Nonlinear evolution equations; Yu-Toda-Sasa-Fukuyama equation; Lie infinitesimals; solitons